2020
DOI: 10.3390/plants9111411
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Recurrent Parent Genome in a Marker-Assisted Backcrossing Against Rice Blast and Blight Infections Using Functional Markers and SSRs

Abstract: The most vital aspect of marker-assisted backcross breeding is the recurrent parent genome recovery. This enables the selection of only parents with recovered recipient/recurrent parent genome in addition to the targeted genes. The recurrent parent genome recovery (RPGR) ensures that non-desirable genomic segments are removed while the gene of interest is sustained in the recombined progenies without further segregations. This work was aimed at quantifying the RPGR of backcross populations with introgression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…The recurrent parent genome recovery in BC 2 F 2 plants was higher (91.3%) in this study as compared to 87.5% genetic similarity to the recurrent parent obtained after two backcrosses through conventional breeding ( Venkatesh et al, 2015 ). A recurrent parent genome recovery of 95.9% in BC 2 F 2 rice plants was reported using polymorphic SSR markers by Chukwu et al (2020) . The marker-assisted backcross breeding is a dynamic approach for conveniently recognizing plants that have recovered over 98% of the recurrent parent genome in two to three backcross generations depending upon the availability of polymorphic markers ( Stojsin 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recurrent parent genome recovery in BC 2 F 2 plants was higher (91.3%) in this study as compared to 87.5% genetic similarity to the recurrent parent obtained after two backcrosses through conventional breeding ( Venkatesh et al, 2015 ). A recurrent parent genome recovery of 95.9% in BC 2 F 2 rice plants was reported using polymorphic SSR markers by Chukwu et al (2020) . The marker-assisted backcross breeding is a dynamic approach for conveniently recognizing plants that have recovered over 98% of the recurrent parent genome in two to three backcross generations depending upon the availability of polymorphic markers ( Stojsin 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, NERICA4 × ST6 lines were observed to have the lowest maximum RPGR at 87.7%. The low RPGR observed in these lines could have been avoided if the analysis was carried out as early as BC 1 generation [ 19 , 41 ]. Nowadays, background selection at an early generation through GBS is cost-efficient for MAB programs.…”
Section: Discussionmentioning
confidence: 99%
“…Since, the majority of gametes in BC1F1 were segregating, random fusion might lead to combinations containing recurrent parent genomes, which could lead to enhanced recovery of RPG at the cost of residual heterozygosity. An MABB study by Chukwu et al, 2020 reported a recurrent parent genome recovery of 80%-86.4% from BC 2 F 1 to 93.2%-98.7% from BC 2 F 2 , after one generation of selfing. Similar reports were presented by Bellundagi et al (2022) for wheat and Miah et al (2015) in rice.…”
Section: Marker-assisted Transfer Of Drought Tolerance Qtlsmentioning
confidence: 99%